LC-ESI-tandem MS and in silico ADMET analysis of polyphenols from Rhus coriaria L. and Micromeria fruticosa (L.) Druce ssp. brachycalyx P. H. Davis - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT (SPRINGER, 2021)
Background: Micromeria fruticosa (L.) Druce ssp. brachycalyx P. H. Davis and Rhus coriaria L., which are Lamiaceae species, are used both as spices in food and medicinally. Lamiaceae species are known to contain high amounts of polyphenols. In this study, liquid chromatography-quadrupole time-of-flight-tandem mass spectrometry (LC-QTOF-MS/MS) was used for analysis of polyphenols in the plants. Under gradient elution with using 0.1% aqueous acetic acid solution and acetonitrile mobile phases, an Agilent Poroshell C18 reversed phase column was used for the simultaneous determination of 18 polyphenols, and separation was performed in 30 min. Pharmacokinetic properties of these polyphenols such as drug-like and toxicity were estimated using open-source software, pkCSM and SwissADME. Results: These compounds were determined to represent different classes of polyphenols, including phenolic acids, flavonoids, coumarin and tannins. ADMET predictions of polyphenols indicated that these compounds are easily absorbed and do not have toxic effects. Conclusion: While the Rhus coriaria L. includes anthocyanidins, tannins, phenolic acid and flavonoids, the Micromeria fruticosa (L.) Druce ssp. brachycalyx P. H. Davis has phenolic acid, coumarin and flavonoids, according to these results. In silico ADME/Tox predictions revealed that these bioactive components are to be drug-like and non-mutagenic. These data are supportive for future analysis that can lead to their therapeutic use of the plants, suggesting that this species may be used as a natural medicinal source in the future after detailed analysis tests.
Keywords: Tandem mass spectrometry; ADMET; Phenolics; Lamiaceae; PHENOLIC-COMPOUNDS; ESSENTIAL OIL; ANTIOXIDANT; COMPONENTS; LAMIACEAE; EXTRACTS; PROFILE; LEAVES